Land Suitability Assessment for Cereal Crops in Sainamaina Municipality Nepal - Gnyawali, Bishal; Aryal, Ishwor; Mandal, Umesh Kumar (The Geographic Base, 2022)
Land suitability is the fitness of a given type of land for a defined use. The land may be considered in its present condition or after improvements. This paper aims to present the land suitability of the study area for major cereal crops. The present study is conducted in ward no. 5, 6, 7, 8 and 9 of Sainamaina municipality Rupandehi district Nepal. Soil samples were taken from 29 different pits from polygon generated by intersecting land system map and land capability map within agricultural land use map with the help of geographic information system. Collected soil samples were tested in the soil laboratory of central department of geography, Tribhuwan University. Land suitability for major cereal crops paddy, wheat, maize and millet were derived from FAO guideline for land evaluation. As a result, the land of study area is found more suitable for wheat followed by paddy maize and millet.